Exploring the Impact of Women Governance on CO2 Emissions in the European Union and Central Asia - Inglesi-Lotz, Roula; Oosthuizen, Anna Maria; Jumaniyazova, Sharifa; Kuziboev, Bekhzod; Liu, Jie (International Journal of Energy Economics and Policy, 2024)
The study is novel to contribute to the literature investigating the relationship among CO2 emissions, women governance, economic development, fossil fuel energy consumption and renewable energy consumption, using a balanced panel dataset of 27 European Union and 4 Central Asian countries over the period 1996-2020. As econometric tools, panel quantile and threshold regression models are employed. Overall, the quantile results document that women governance help to mitigate climate change both in European Union and Central Asia. Moreover, threshold findings suggest that women governance negatively impact on CO2 emissions in European Union and Central Asia when economic growth is higher than 9.903 percent. Policy implications are proposed to enhance women governance in European Union and Central Asia.